Analisis Sistem Pencatatan Bahan Baku dalam Proses Produksi - Dindan Mega Aprilia (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
The purpose of this study was to identify the advantages and disadvantages of each method and formulate recommendations for improvements to enhance operational efficiency. Through a qualitative approach involving participant observation, semi-structured interviews, and internal document analysis during the internship period from February to June 2025, findings indicated that the manual method was prone to input errors, information delays, and a lack of integration between divisions, while Jurnal.id offered advantages in real-time recording and data accuracy. The evaluation results confirmed that the digital transition had a significant positive impact on inventory control. As a transition solution, a hybrid model combining manual and digital elements was recommended, supported by employee training, the development of standard operating procedures (SOPs), and infrastructure improvements. This study contributes to the understanding of technology adaptation in medium-sized manufacturing companies in Indonesia and serves as a reference for similar entities in facing the challenges of digitalization